Спогади військового міністра УНР генерала Грекова - Тинченко, Я. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The former Minister of War of Ukranian People’s Republik and the Commander of Ukrainian Galician Army, general Oleksandr Hrekov (1875–1959) was arrested by Soviet intelligence service in Vienna in 1948 and sentenced to 25 years of hard labour camp. After having been released in 1956 he returned to Austria, where he died soon afterwards. Here we published memoirs of general, which were.